Dynamic Heat Transfer Modeling and Validation of Super-Long Flexible Thermosyphons for Shallow Geothermal Applications - Jianhua Liu; Yanghuiqin Ding; Hao Liu; Liying Zheng; Xiaoyuan Wang; Yuezhao Zhu (Energies)
In comparison to borehole heat exchangers that rely on forced convection, super-long thermosyphons offer a more efficient approach to extracting shallow geothermal energy. This work conducted field tests on a super-long flexible thermosyphon (SFTS) to evaluate its heat transfer characteristics. The tests investigated the effects of cooling water temperature and the inclination angle of the condenser on the start-up characteristics and steady-state heat transfer performance. Based on the field test results, the study proposed a dynamic heat transfer modeling method for SFTSs using the equivalent thermal conductivity (ETC) model. Furthermore, a full-scale 3D CFD model for geothermal extraction via SFTS was developed, taking into account weather conditions and groundwater advection. The modeling validation showed that the simulation results aligned well with the temperature and heat transfer power variations observed in the field tests when the empirical coefficient in the ETC model was specified as 2. This work offers a semi-empirical dynamic heat transfer modeling method for geothermal thermosyphons, which can be readily incorporated into the overall simulation of a geothermal system that integrates thermosyphons.